A new species of Haliplus Latreille, 1802 from Cuba (Coleoptera: Haliplidae). Issue 1 (2nd January 2018) - Megna, Yoandri S.; Hendrich, Lars; Balke, Michael
ABSTRACT: Haliplus alberti sp. n. is described, based on three specimens collected in Pan de Guajaibon, San Juan de Sagüa, Pinar del Río, Cuba. Morphologically, the new species is similar to H. pseudofasciatus Wallis, 1933 and H. mutchleri Wallis, 1933, both from Florida (USA). The beetles were collected in a permanent lagoon with abundant aquatic vegetation, muddy bottom and macrophytes near the banks. Seven species of Haliplus are now known from Cuba. http://zoobank.org/urn:zoobank.org:pub:3CE6BA24-9D20-4A4D-8C8A-51687B750244